Front Cover: Tracking Ionic Rearrangements and Interpreting Dynamic Volumetric Changes in Two‐Dimensional Metal Carbide Supercapacitors: A Molecular Dynamics Simulation Study (ChemSusChem 12/2018). Issue 12 (21st June 2018) - Xu, Kui; Lin, Zifeng; Merlet, Céline; Taberna, Pierre‐Louis; Miao, Ling; Jiang, Jianjun; Simon, Patrice
Abstract : The Front Cover shows a molecular dynamics simulation study performed on two‐dimensional Ti3 C2 T x MXene‐based supercapacitor in the ionic liquid 1‐ethyl‐3‐methylimidazolium bis(trifluoromethylsulfonyl)imide ([EMIM] + [TFSI] − ) as electrolyte in combination with an in situ XRD experiment for verification. The simulations reproduce the different patterns of volumetric change observed experimentally for both the negative and positive electrodes. The analysis of ionic fluxes and structure rearrangements in the 2D material provide an atomic‐scale insight into the charge and discharge processes in the layer pore and confirm the existence of two different charge‐storage mechanisms at the negative and positive electrodes. Changes in ionic number and structural rearrangement contribute to the dynamic volumetric changes of both electrodes: negative electrode expansion and positive electrode shrinkage. More information can be found in the Full Paper by Xu et al. on page 1892 in Issue 12, 2018 (DOI: 10.1002/cssc.201702068 ).